Emergence and dissemination of multidrug-resistant Klebsiella pneumoniae harboring the novel tmexCD-toprJ RND efflux pump operon - Gao, Haojin; Wang, Bingjie; Li, Meilan; Zhou, Peiyao; Wu, Chunyang; Wan, Cailing; Shen, Li; Fu, Jiana; Han, Weihua; Zhou, Ying; Yu, Fangyou (Frontiers in Cellular and Infection Microbiology, 2025)
The global emergence of multidrug-resistant (MDR) Klebsiella pneumoniae, particularly carbapenem-resistant K. pneumoniae (CRKP), presents a severe public health threat, limiting available treatment options. Tigecycline and eravacycline, have been considered a last-resort therapeutic against MDR Enterobacteriaceae. However, strains were resistant to these antibiotics increased recently. The tmexCD-toprJ, a plasmid-encoded resistance-nodulation-division (RND)-type efflux pump, has emerged as a critical factor conferring resistance to tigecycline and eravacycline. In this study, we reported the emergence of 11 CRKP isolates harboring tmexCD-toprJ, isolated from two lung transplant patients in a tertiary hospital in eastern China. Most of the isolates (82%) exhibited high-level resistance to tigecycline and eravacycline, along with other common antibiotics. Whole-genome sequencing (WGS) and phylogenetic analysis indicated these strains are not clonal, and resistance phenotypes were associated with the tmexCD-toprJ operon and other crucial resistance elements. We also found the tmexCD-toprJ operon was located on a conjugative plasmid, sharing high sequence similarity with the operon identified in Pseudomonas aeruginosa. Our results showed that the tmexCD-toprJ-harboring plasmid is efficiently transferable, which contributes to the dissemination of tigecycline and eravacycline resistance. At the same time, the plasmid can coexist with the blaKPC-2-carrying plasmid, which may cause multidrug resistance. The emergence of tmexCD-toprJ-positive CRKP in lung transplant patients highlights the potential for rapid nosocomial dissemination and reduced treatment efficacy of last-line antimicrobials. Our findings emphasize the need for enhanced genomic surveillance, infection control measures, and alternative therapeutic strategies to combat the spread of tmexCD-toprJ-mediated resistance in clinical settings.